Comparison of hyaluronic acid in patients with rheumatoid arthritis, systemic sclerosis and systemic lupus erythematosus - Cylwik, Bogdan (Array, 2021)
The aim of the present study was to determine and compare the concentration of hyaluronic acid (HA) in rheumatoid arthritis (RA), systemic sclerosis (SSc) and systemic lupus erythematosus (SLE), and its correlation with parameters of disease activity and duration. The hypothesis was that HA should be increased in rheumatic diseases. We also expected that HA could be a marker of disease activity and inflammation in some of these diseases.The study group comprised 149 patients with RA, SSc and SLE hospitalized in the Department of Rheumatology and Internal Diseases, Medical University of Bialystok (Bialystok, Poland) and 30 healthy controls. The concentrations of HA, C-reactive protein (CRP) and rheumatoid factor (RF) were measured using Architect ci8200; haemoglobin, platelets on Sysmex XS-800i; and erythrocyte sedimentation rate (ESR) on Sediplus S 2000 analysers. Statistical analysis was performed using Statistica 13.3 PL.Hyaluronic acid was increased in RA, SLE and SSc when compared to controls (P <0.001, P = 0.011, and P = 0.015, respectively). There were no differences in HA between rheumatic diseases (P = 0.840). Hyaluronic acid positively correlated with SLE activity (P = 0.025). In RA, HA positively correlated with ESR (P = 0.028) and CRP (P = 0.009). However, HA was not found to correlate with the duration of rheumatic diseases.Hyaluronic acid concentration undergoes changes in rheumatic diseases with no difference between RA, SLE and SSc. In RA, HA concentration can be a marker of inflammation, while in SLE patients an indicator of disease activity.